Effect of vitamin d on treatment of malignant tumor - Anna Małgorzata Łopuszyńska; Bartłomiej Pawlicki; Mateusz Maciej Pawlicki; Karol Lorenc; Magdalena Kozioł; Zofia Misztal (Kazimierz Wielki University, 2019)
Vitamin D is a group of steroid organic chemicals that are fat-soluble. The most important are two forms of vitamin D, which are ergocalciferol (vitamin D2) occurring naturally in plant organisms as well as yeast and cholecalciferol (vitamin D3) found naturally in animal organisms. This vitamin is known primarily for its effects on the skeletal system, where it affects the calcium-phosphate economy, and also constitutes a bone component. As a result, it is mainly used in the prevention and treatment of rickets or osteoporosis. Recent clinical and epidemiological studies suggest that vitamin D has other uses as well. More and more research confirms that its deficiency increases the risk of malignant tumor and is associated with worse prognosis. Therefore, vitamin D supplementation may have an impact on reducing the number of cases and may increase the chances of recovery. It has been found that vitamin D inhibits the proliferation and formation of malignant tumor cells, can induce their apoptosis and has an effect on angiogenesis and metastasis. WHO estimates that in 2018 around 9.6 million people have died of malignant tumors and the number of patients in the world is constantly increasing. Therefore, the use of vitamin D in their treatment can be a breakthrough solution. Its low price, availability, or known and low toxicity speak for its use in the discussed purposes. Still, more research is needed to develop an effective anticancer drug with its participation.